DYNAMICS OF EMPLOYEE VOICE, OCB, AND CONFLICT RESOLUTION ON EMPLOYEE RETENTION IN PRIVATE - Eliana Priscilla Hidayat; Fatmah Bagis; Hengky Widhiandono; Dian Widyaningtyas (JURNAL ILMIAH EDUNOMIKA, 2026)
The retention of healthcare personnel has emerged as a strategic challenge for hospitals, particularly in the post-pandemic era marked by increased workloads and more complex organizational dynamics. Rising professional demands require hospitals to adopt more adaptive human resource management practices. This study examines the role of employee voice and organizational citizenship behavior (OCB) in employee retention, with conflict resolution as a mediating variable, in private hospitals in Purwokerto. The research focuses on permanent employees directly involved in hospital service delivery. Using a quantitative survey approach, data were collected from 240 respondents out of a population of 542 employees and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that employee voice does not have a significant direct effect on employee retention, although it positively influences conflict resolution. In contrast, OCB has a significant positive effect on both conflict resolution and employee retention. Furthermore, conflict resolution positively affects employee retention and mediates the relationships between employee voice and employee retention, as well as between OCB and employee retention. These findings support Social Exchange Theory, highlighting that positive social exchanges, reflected through prosocial behavior and effective conflict resolution, can enhance employee commitment and intention to remain in the organization. Practically, the study suggests that hospitals should foster open communication, strengthen conflict resolution capabilities, and encourage extra-role behaviors to retain high-quality healthcare personnel.